Parental Factors Influencing the Development of Early Childhood Caries in Developing Nations: A Systematic Review - Rai, Nayanjot Kaur; Tiwari, Tamanna (Frontiers in Public Health, 2018)
Background Early childhood caries (ECC) is one of the most prevalent and chronic conditions of childhood. Various factors including biological and dietary factors along with an overlay of parental social factors have been found to be associated with the progression of ECC. The objective of this systematic review is to synthesize available literature and to identify parent-level proximal and distal risk factors associated with the development of ECC in developing nations. Methods Studies conducted in developing nations, published between 2005 and 2017 in English, that included children younger than 6 years and examined ECC were included. The outcome of interest were parental risk factors, which included parental knowledge, behavior, attitudes, sense of coherence (SOC), stress, socioeconomic status (SES), education, and breastfeeding duration. The studies were retrieved from MEDLINE, Ovid Medline, and PubMed. Results The search yielded 325 studies, of which 18 were considered eligible for inclusion in this review. Ten studies found maternal education, and seven studies found parental education to be significantly associated with ECC. SES was significantly associated with ECC in 13 studies in the form of annual household income and occupation level. Four studies observed the significant association between oral health knowledge and attitudes with ECC, whereas only two studies found maternal attitude to be associated with ECC. Breastfeeding duration was a significant risk factor in four studies. One study each found significant associations of SOC, parental distress, and secondary smoke with ECC. Conclusion To date, most of the researches done in developing countries have reported distal parental factors such as income and education being significant risk factors in caries development compared to proximal risk factors in low-income groups. Only a few studies analyzed the psychosocial and behavioral factors. Interventions could be designed to improve parental oral health knowledge and behaviors in these nations.